Asymptomatic group A Streptococcal throat carriage in Royal Marines recruits and Young Officers. Issue 6 (June 2017) - Pearson, M.; Fallowfield, J.L.; Davey, T.; Thorpe, N.M.; Allsopp, A.J.; Shaw, A.; Wilson, D.R.; Sriskandan, S.; Lamb, L.E.
Summary: Aims: A prospective observational study was conducted in Royal Marines (RM) recruits to investigate throat carriage of group A Streptococcus (GAS) and incidence of soft tissue infections. Methods: 1012 RM recruits were followed through a 32-week training programme, with throat swabs being obtained in weeks 1, 6, 15, and 32. Alongside a separate cohort of 46 RM Young Officers (YO) undergoing training were sampled in parallel. Results: Carriage of group A Streptococcus was detected in only 5/1012 (0.49%) recruits at the beginning of training and remained low throughout training. There was no association between GAS carriage and development of soft tissue infection. There was no carriage of GAS in the smaller YO cohort at the start of training, (0/46). At week 6, a surge in GAS carriage was detected in 8/46 (17%) YO, that could be ascribed to a cluster of GAS genotype emm 83. Conclusions: Asymptomatic GAS carriage is very infrequent among young adults in England and this should be borne in mind when considering the relevance of a positive throat swab result in symptomatic patients or outbreaks. Despite low prevalence, there is however potential for GAS to rapidly and transiently disseminate among adults during outbreaks.